The mouth in HIV/AIDS: markers of disease status and management challenges for the dental profession - Johnson, NW (Australian dental journal, 2010)
There are over 30 million people in the world with HIV infection and, whilst the rate of new infections is slowing, this number continues to grow. Although in Australia the overall prevalence of HIV infection in adults aged 15–49 is officially estimated at only 0.2%, representing less than 20 000 people living with HIV and AIDS, our geographical area contains populations with prevalences exceeding 10 times this. Oral health professionals must therefore practise safe, standard infection control at all times and be aware of the oral manifestations of HIV disease. These are predominantly opportunistic infections with fungi such as Candida albicans or with viruses of the herpes family, particularly herpes simplex, herpes zoster and Epstein‐Barr virus infections. Warts or papillomas may arise due to human papilloma viruses – even in individuals on effective antiretroviral therapy. Rare types of fungal infection can occur, and severe bacterial infections, notably tuberculosis, are an ever‐present risk. Susceptibility to periodontal breakdown is somewhat enhanced by the effects of HIV disease itself, and caries activity may increase because the patient neglects attention to diet and oral hygiene. Restorative and periodontal care need, therefore, to be maintained at a high level. Oral opportunistic infections cause much distress and the diagnosis and management of these is the responsibility of our profession.